It would be
y=(-16*-1)
which would then be
y=16
so the answer would be
(-16,16)
you replace the x in the equation with the x you are given
First we need to factor the left side. Since it is a perfect square (as is the process with completing the square, we know we can take half of the middle number along with x to be in the two parenthesis.
(x - 4)(x - 4) = 25
Now we simplify to show it as a square.
(x - 4)^2 = 25
Next we take the square root of both sides
x - 4 = +/- 5
Note that we have plus or minus 5. This is because either square would give us positive 25. Now we add 4 to both sides
x = 4 +/- 5
4 + 5 = 9
4 - 5 = -1
Answer:
n=3
Step-by-step explanation:
Operation used is division
Answer:
give me brainliest now plsssss
Step-by-step explanation:
(8x-22)=5x+29
We move all terms to the left:
(8x-22)-(5x+29)=0
We get rid of parentheses
8x-5x-22-29=0
We add all the numbers together, and all the variables
3x-51=0
We move all terms containing x to the left, all other terms to the right
3x=51
x=51/3
x=17